Radionuclide Treatments - Soydal, Cigdem (IntechOpen, 2017)
This book has been designed to give a brief information on the development and current status of radionuclide treatments. Today, despite most of them have been accepted experimentally in the clinical guidelines, the number of the radionuclide treatments has been increasing gradually. Theranostic concept is the leading cause for this increase. Behind the radioiodine treatment for benign and malignant thyroid diseases, other radionuclide treatments that consist of I-131 metaiodobenzylguanidine therapy for neuroectodermal tumors, radionuclide pain palliation for bone metastases, radiosynovectomy, and selective internal radiation therapy were included in the book. All the chapters have been written by experienced nuclear medicine physicians.